Enhanced heroin analgesic effect in male offspring of sires who self-administered heroin - Wenjing Gao; Tao Pan; Guangyuan Fan; Jian Cui; Tingting Wang; Nan Huang; Changyou Jiang; Lan Ma; Feifei Wang; Xing Liu; Qiumin Le (Frontiers in Pharmacology, 2023)
Introduction: A growing body of evidence suggests that parental substance abuse, even prior to conception, may induce phenotypic changes in offspring. Parental opioid exposure has been shown to affect developmental processes, induce memory deficits, and lead to psycho-emotional disorders in offspring. However, how parental, especially paternal, chronic drug exposure affects offspring remains unexplored.Methods: Adult male rats were subjected to 31 days of heroin self-administration followed by mating with naïve females. Litter size and body weight of F1 offspring were recorded. Object-based attention tests, cocaine self-administration tests, and hot plate tests were used to test for potential effects of chronic paternal heroin seeking on cognition, reward, or analgesic sensitivity in the offspring.Results: Body weight and litter size of the heroin F1 generation were not altered compared to the saline F1 generation. Furthermore, paternal chronic heroin self-administration experience had no significant effect on object-based attention tests or cocaine self-administration behavior in either sex. However, in the hot plate test, although no difference in basal latency was found between the two groups in either sex, a significant increase in the analgesic effect of heroin was observed in the male heroin F1 generation.Conclusions: Taken together, these data provide evidence that paternal chronic heroin self-administration experience could sex-dimorphically increase the analgesic effect of heroin in male offspring, but had no significant effect on response to cocaine reinforcement or attentional behavior.